Pelatihan Aplikasi Publish or Perish dan Vosviewer untuk Optimalisasi Percepatan Kelulusan Mahasiswa Tingkat Akhir - Neny Desriani; Joni Putra; Aryan Danil Mirza. BR; Diajeng Fitri Wulan (BADAN PENERBIT STIEPARI PRESS, 2025)
Delays in the graduation of final-year students remain a common problem in higher education. One of the causes is low academic literacy, particularly in literature searches and bibliography compilation. To address this issue, this community service activity was carried out through training in the use of the Publish or Perish (PoP) and VOSviewer applications. The training was held at the Accounting Computer Laboratory of the University of Lampung using a participatory workshop method that emphasized hands-on practice and intensive mentoring. A total of 20 final year students from the Accounting Study Program were involved in this activity. The evaluation results showed a significant increase in participants' understanding. Students were able to compile more systematic literature reviews and identify research gaps in their respective fields of study. This activity also had an impact on increasing student motivation in completing their theses and reducing the technical burden on supervising lecturers. Thus, PoP and VOSviewer training proved to be effective in strengthening academic literacy, supporting graduation acceleration, and encouraging a culture of research in higher education. Moving forward, similar programs can be expanded to other study programs and integrated with scientific article writing training.